A Genome‐Wide Association Study of Early Spontaneous Preterm Delivery. Issue 3 (19th January 2015) - Zhang, Heping; Baldwin, Don A.; Bukowski, Radek K.; Parry, Samuel; Xu, Yaji; Song, Chi; Andrews, William W.; Saade, George R.; Esplin, M. Sean; Sadovsky, Yoel; Reddy, Uma M.; Ilekis, John; et al.
ABSTRACT Preterm birth is the leading cause of infant morbidity and mortality. Despite extensive research, the genetic contributions to spontaneous preterm birth (SPTB) are not well understood. Term controls were matched with cases by race/ethnicity, maternal age, and parity prior to recruitment. Genotyping was performed using Affymetrix SNP Array 6.0 assays. Statistical analyses utilized PLINK to compare allele occurrence rates between case and control groups, and incorporated quality control and multiple‐testing adjustments. We analyzed DNA samples from mother–infant pairs from early SPTB cases (200/7–336/7 weeks, 959 women and 979 neonates) and term delivery controls (390/7–416/7 weeks, 960 women and 985 neonates). For validation purposes, we included an independent validation cohort consisting of early SPTB cases (293 mothers and 243 infants) and term controls (200 mothers and 149 infants). Clustering analysis revealed no population stratification. Multiple maternal SNPs were identified with association P‐values between 10 × 10–5 and 10 × 10–6. The most significant maternal SNP was rs17053026 on chromosome 3 with an odds ratio (OR) 0.44 with a P‐value of 1.0 × 10–6. Two neonatal SNPs reached the genome‐wide significance threshold, including rs17527054 on chromosome 6p22 with a P‐value of 2.7 × 10–12 and rs3777722 on chromosome 6q27 with a P‐value of 1.4 × 10–10. However, we could not replicate these findings after adjusting for multiple comparisons in a validation cohort. This is the first report of a genome‐wide case‐control study to identify single nucleotide polymorphisms (SNPs) that correlate with SPTB.